Reinvestigation of trilithium divanadium(III) tris(orthophosphate), Li(3)V(2)(PO(4))(3), based on single-crystal X-ray data - Kee, Yongho (International Union of Crystallography, 2013)
The structure of Li(3)V(2)(PO(4))(3) has been reinvestigated from single-crystal X-ray data. Although the results of the previous studies (all based on powder diffraction data) are comparable with our redetermination, all atoms were refined with anisotropic displacement parameters in the current study, and the resulting bond lengths are more accurate than those determined from powder diffraction data. The title compound adopts the Li(3)Fe(2)(PO(4))(3) structure type. The structure is composed of VO(6) octahedra and PO(4) tetrahedra by sharing O atoms to form the three-dimensional anionic framework (∞) (3)[V(2)(PO(4))(3)](3−). The positions of the Li(+) ions in the empty channels can vary depending on the synthetic conditions. Bond-valence-sum calculations showed structures that are similar to the results of the present study seem to be more stable compared with others. The classical charge balance of the title compound can be represented as [Li(+)](3)[V(3+)](2)[P(5+)](3)[O(2−)](12).